Upfront fixed-duration treatment strategies for chronic lymphocytic leukemia in Arab populations: a position statement from the Gulf region - Yassin, Mohamed A.; Al Farsi, Khalil; Hamad, Anas; Ghasoub, Rola; Alhuraiji, Ahmad; Mheidly, Kayane; Yaseen, Hasan Aal; Osman, Hani; Trepel, Martin (Frontiers in Medicine, 2025)
The treatment landscape for chronic lymphocytic leukemia (CLL) has expanded dramatically over the last decade, with a wide range of effective treatments now available. Clinical management of CLL varies widely depending on patient profile, meaning the optimal treatment in Arab patients, who tend to be young and often present with comorbidities, including diabetes and obesity, requires specific considerations. In the absence of regional guidelines, a group of experts from across the Gulf region and one international expert from Germany convened to discuss and agree upon a position statement for venetoclax-based fixed-duration treatment strategies for Arab patients with CLL. Our position is that ibrutinib-venetoclax should be the first choice as first-line therapy for all fit CLL patients in the region, regardless of age. The advantages of an all-oral, fixed-duration treatment are discussed in the context of a young Arab patient population, including excellent patient and physician convenience, limited accumulative risk of toxicities, uncomplicated logistics, and low burden of healthcare administration costs. Finally, we discuss the management of key safety considerations in Arab populations including ethnic neutropenia, risk of cardiotoxic events, considerations during intermittent fasting, and avoiding adverse drug–drug interactions, e.g., with anti-tuberculosis or anti-obesity medications.